Cerebellar Culture Models of Dendritic Spine Proliferation After Transplantation of Glia. (1997) - Seil, Fredrick J.
Abstract : Studies of Purkinje cell dendritic spine proliferation after transplantation of cytosine arabinoside (Ara C) treated organotypic cerebellar cultures with glia and granule cells, either separately and in combination, were reviewed. Exposure of cerebellar explants to Ara C for the first 5 days in vitro results in the destruction of granule cells, the only excitatory cortical neurons, and oligodendroglia, and functionally compromises surviving astrocytes so that they do not appose neuronal membranes. In the absence of granule cells, there is a sprouting of Purkinje cell recurrent axon collaterals, the terminals of which project to and form heterotypical synapses with Purkinje cell dendritic spines, which are usually occupied by terminals of granule cell axons (parallel fibers). After this reorganization has been achieved, the explants can be transplanted with the missing elements to induce a second round of reorganization, with approximate restoration of the usual interneuronal relationships. Addition of both granule cells and glia resulted in a proliferation of clusters of Purkinje cell dendritic spines, which formed synapses with axon terminals of transplanted granule cells, and as synapse formation progressed, the spine clusters became reduced. Transplantation of Ara C-treated cultures with glia alone resulted in a proliferation of clusters of Purkinje cell dendritic spines, but in the absence of granule cells the spines remained unattached, and the clusters persisted throughout the period of observation. Purkinje cell dendritic spine proliferation was induced by exposure of Ara C-treated cultures to astrocyte-conditioned medium. When Ara C-treated cerebella cultures were transplanted with granule cells in the absence of functional glia, parallel fiber- Purkinje cell dendritic spine synapses formed, but no clusters of Purkinje cell dendritic spines were observed. These findings suggest that Purkinje cell dendritic spine proliferation is induced by an astrocyte-secreted factor, resulting in an expansion of postsynaptic sites available for synaptogenesis.